Aggregation‐Dependent Dielectric Permittivity in 2D Molecular Crystals. Issue 4 (17th February 2022) - Yang, Yutian; Wang, Yingying; Qiao, Jingsi; Zhao, Weiwei; Yu, Yuanfang; Feng, Shaopeng; An, Xuhong; Zhang, Jialin; Ji, Wei; Wang, Xinran; Lu, Junpeng; Ni, Zhenhua
Abstract: The functionality of 2D molecular crystal‐based devices crucially depends on their intrinsic properties, such as molecular energy levels, light absorption efficiency, and dielectric permittivity, which are highly sensitive to molecular aggregation. Here, it is demonstrated that the dielectric permittivity of the 2, 7‐dioctyl[1]benzothieno[3, 2‐b][1]benzothiophene (C8 ‐BTBT) molecular crystals on monolayer WS2 substrates can be tuned from 4.62 in the wetting layer to 2.25 in the second layer. Its origin lies in the different molecular orientations in the wetting layer (lying‐down) and in the subsequently stacked layers (standing‐up), which lead to a positive Coulomb coupling ( JCoup ) value (H‐aggregation) and a negative JCoup value (J‐aggregation), respectively. Polarized optical contrast spectroscopy reveals that the permittivity of C8 ‐BTBT is anisotropic, and its direction is related to the underlying substrate. The study offers guidelines for future manipulation of the permittivity of 2D molecular crystals, which may promote their applications toward various electronic and optoelectronic devices. Abstract : The dielectric permittivity of the C8 ‐BTBT molecular crystal on monolayer WS2 substrate can be tuned from 4.62 in the wetting layer to 2.25 in the second layer. The polarized optical contrast spectroscopy reveals that the permittivity of the C8 ‐BTBT is anisotropic, and its direction is related to the underlying substrate.